A facile method to fabricate high performance PVA/PAA-AS hydrogel via the synergy of multiple hydrogen bonding and Hofmeister effect. Issue 2 (22nd January 2023) - Liu, Zexin; Hu, Yinchun; Gong, Yue; Cheng, Yizhu; Yang, Hui; Kang, Min; Ding, Huixiu; Lei, Zhipeng; Wei, Yan; Huang, Di
Abstract: Hydrogels are widely used in biomedical engineering, which often require matched mechanical properties to meet specific demands. Recently, numerous research studies have contributed to tissue engineering hydrogels by soaking strategies to obtain designed properties. Herein, a strategy to fabricate poly(vinyl alcohol)/poly(acrylic acid)-ammonium sulfate (PVA/PAA-AS) hydrogel by successively soaking an aqueous PAA solution and (NH4 )2 SO4 solution based on the synergy of multiple hydrogen bonding and Hofmeister effect is reported, which exhibits remarkable comprehensive mechanical properties: rigidity (elastic modulus: 0.7–3.6 MPa ), strength at break (tensile stress: 3.2–12.0 MPa ; strain 320–650%), and toughness (fracture energy: 4.5–30.0 MJ m − 3 ). Besides, PVA/PAA-AS hydrogel with unique spring-like microstructure exhibited super-resilience in 30% strain range by energy-transforming mechanism. Compared with pure PVA hydrogel, PVA/PAA-AS hydrogel has the equal excellent cytocompatibility. Therefore, PVA/PAA-AS hydrogel with high strength, modulus, toughness, super-resilience and excellent biocompatibility has potential applications in the soft tissue engineering field such as muscles, tendons, and ligaments.